In Vitro/Vivo Mechanisms of Antibacterial Peptide NZ2114 against Staphylococcus pseudintermedius and Its Biofilms - Shuang Zhang; Na Yang; Ruoyu Mao; Ya Hao; Da Teng; Jianhua Wang (MDPI AG, 2024)
Staphylococcus pseudintermedius is an opportunistic pathogen commonly found in canines, and has garnered escalating interest due to its potential for zoonotic transmission and increasing antimicrobial resistance. However, the excessive use of antibiotics and the characteristic of S. pseudintermedius forming biofilms make treatment challenging. In this study, the in vivo and in vitro antimicrobial activity and mechanisms of action of NZ2114, a plectasin-derived peptide, against S. pseudintermedius were investigated. NZ2114 exhibited potent antibacterial activity towards S. pseudintermedius (minimum inhibitory concentration, MIC = 0.23 μM) with a lower probability of inducing drug-resistant mutations and efficient bactericidal action, which was superior to those of mopirucin (MIC = 0.25-0.5 μM) and lincomycin (MIC = 4.34-69.41 μM). The results of electron microscopy and flow cytometry showed that NZ2114 disrupted S. pseudintermedius' cell membrane, resulting in cellular content leakage, cytoplasmic membrane shrinkage, and, eventually, cell death. The intracellular ROS activity and Alamar Blue detection showed that NZ2114 interferes with intracellular metabolic processes. In addition, NZ2114 effectively inhibits biofilm formation, and confocal laser scanning microscopy further revealed its antibacterial and anti-biofilm activity (biofilm thickness reduced to 6.90-17.70 μm). The in vivo therapy of NZ2114 in a mouse pyoderma model showed that it was better than lincomycin in effectively decreasing the number of skin bacteria, alleviating histological damage, and reducing the skin damage area. These results demonstrated that NZ2114 may be a promising antibacterial candidate against S. pseudintermedius infections.